Hydrogen concentrator demonstrator module with 19.8% solar-to-hydrogen conversion efficiency according to the higher heating value. (26th October 2017) - Fallisch, Arne; Schellhase, Leon; Fresko, Jan; Zedda, Mario; Ohlmann, Jens; Steiner, Marc; Bösch, Armin; Zielke, Lukas; Thiele, Simon; Dimroth, Frank; Smolinka, Tom
Abstract: Renewable hydrogen is a key element to a sustainable energy system of the future. Therefore solar hydrogen generation has been investigated by various research groups in recent years. The patented concept of the Hydrogen Concentrator (HyCon), which combines III-V multi-junction solar cells with polymer electrolyte membrane electrolysis, has been constantly developed over the last years. In this work, a unique weatherproof HyCon module with an area of 8 × 90.7 cm 2 was build and characterized in an outdoor measurement for over two month. During this measurement period, the module showed a stable operation regardless of the water volume flow. The module works under natural convection without any circulation pumps at a suitable maximum temperature of 60–70 °C. The HyCon module consists of eight individual units (HyCon cells), each combining a photovoltaic and an electrolysis cell. Some of the HyCon cells reach a solar-to-hydrogen conversion efficiency of 20% according to the higher heating value at high current densities of 0.8 A/cm 2 . On the module level a maximum efficiency of 19.8% is reached. To the best of our knowledge this is the highest conversion efficiency so far achieved at such high current densities using a dual junction solar cell. Highlights: HyCon demonstrator module consisting of 8 cells working under natural convection. High current densities of more than 0.9 A/cm 2 . Solar-to-hydrogen conversion efficiency of 19.8% according to the higher heating value on module level.